1996
DOI: 10.1002/j.1552-4604.1996.tb04196.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Epoprostenol on Drug Disposition II: A Pilot Study of the Pharmacokinetics of Furosemide with and without Epoprostenol in Patients with Congestive Heart Failure

Abstract: The effect of epoprostenol on the pharmacokinetics of furosemide was investigated in 23 patients with end-stage congestive heart failure (CHF) receiving conventional therapy alone or conventional therapy plus epoprostenol. Estimates of the apparent oral clearance, volume of distribution, and absorption rate constant for furosemide were generated from 198 serum furosemide concentrations using nonlinear mixed effects modeling (NONMEM). Univariate analyses were performed to assess the effects of patient factors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Sometimes, a large residual variability in the population pharmacokinetic model along with a relatively small number of pharmacokinetic samples precluded further analysis 71 …”
Section: Population‐based Methods Of Evaluating Drug‐drug Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes, a large residual variability in the population pharmacokinetic model along with a relatively small number of pharmacokinetic samples precluded further analysis 71 …”
Section: Population‐based Methods Of Evaluating Drug‐drug Interactionsmentioning
confidence: 99%
“…70 Sometimes, a large residual variability in the population pharmacokinetic model along with a relatively small number of pharmacokinetic samples precluded further analysis. 71 Factors such as the number and timing of pharmacokinetic sampling points are thus essential to the successful completion of population-based assessments. Ideally, the number and timing of sampling points can be determined using optimal sampling theory.…”
Section: Potential Limitations and Important Points To Considermentioning
confidence: 99%
“…66 A similar study evaluating epoprostenol and furosemide showed that the clearance of furosemide was decreased by 13% when concomitantly administered with epoprostenol but this effect was neither statistically nor clinically significant. 67…”
Section: Epoprostenolmentioning
confidence: 99%